Copper(II)-Assisted Degradation of Pheophytin a by Reactive Oxygen Species - Orzeł, Łukasz; Drzewiecka-Matuszek, Agnieszka; Rutkowska-Zbik, Dorota; Krasowska, Aneta; Fiedor, Leszek; van Eldik, Rudi; Stochel, Grażyna (International Journal of Molecular Sciences, 2024)
The central ion Mg2+ is responsible for the differences between chlorophyll a and its free base in their reactivity toward metal ions and thus their resistance to oxidation. We present here the results of spectroscopic (electronic absorption and emission, circular dichroism, and electron paramagnetic resonance), spectroelectrochemical, and computational (based on density functional theory) investigations into the mechanism of pheophytin, a degradation that occurs in the presence of Cu ions and O2. The processes leading to the formation of the linear form of tetrapyrrole are very complex and involve the weakening of the methine bridge due to an electron withdrawal by Cu(II) and the activation of O2, which provides protection to the free ends of the opening macrocycle. These mechanistic insights are related to the naturally occurring damage to the photosynthetic apparatus of plants growing on metal-contaminated soils.
CRIS-Team Scopus Importer:2024-02-23
Keywords: copper(II); linear tetrapyrrole formation; pheophytin a; reactive oxygen species